Respostas
respondido por:
2
2*( -5 -3x) + 3*( 2x -1) ≤ 2x+1
-10-6x+6x-3≤ 2x+1
-10-3≤ 2x+1
-13≤ 2x+1
-13-1≤ 2x
-14≤ 2x
-14/2≤x
-7≤ x
x vai ser maior ou igual a -7
-10-6x+6x-3≤ 2x+1
-10-3≤ 2x+1
-13≤ 2x+1
-13-1≤ 2x
-14≤ 2x
-14/2≤x
-7≤ x
x vai ser maior ou igual a -7
respondido por:
1
2(5-3x)+3(2x-1)<2x+1
-10-6x+6x-3<2x+1
-6x+6x-2x<1+3+10
-2x<14
-10-6x+6x-3<2x+1
-6x+6x-2x<1+3+10
-2x<14
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás